2003
DOI: 10.1007/bf03179872
|View full text |Cite
|
Sign up to set email alerts
|

The effect of thyroid hormones on blood insulin level and metabolic parameters in diabetic rats

Abstract: The effect of exogenous thyroid hormones on blood insulin and metabolic parameters in diabetic rats was investigated. Three groups of rats were treated with streptozotocin (STZ; 50 mg/kg b.w., intravenously) and one group receiving only saline served as control. Beginning with the third day after STZ treatment, until the last day before decapitation, i.e. for 11 days, two groups of diabetic rats were treated with T3 (50 microg/kg b.w., i.p.) or T4 (250 microg/kg b.w., i.p.). After two weeks, STZ injected rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…In spite of the hypervascularization and immune cells infiltration in pancreas of female rabbits, we previously showed that neither insulin nor glucose levels are affected by hypothyroidism [ 3 ]. It is probable that a long time of treatment with methimazole may result in hyperglycemia and hyperinsulinemia because the treatment with thyroid hormones reduces the hyperglycemia of diabetic rats [ 48 ]. Thus, our present findings (inflammation, changes in vascularization, and immune cells infiltration into the islets) could appear before consolidating hyperinsulinemia and a hyperglycemic status.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the hypervascularization and immune cells infiltration in pancreas of female rabbits, we previously showed that neither insulin nor glucose levels are affected by hypothyroidism [ 3 ]. It is probable that a long time of treatment with methimazole may result in hyperglycemia and hyperinsulinemia because the treatment with thyroid hormones reduces the hyperglycemia of diabetic rats [ 48 ]. Thus, our present findings (inflammation, changes in vascularization, and immune cells infiltration into the islets) could appear before consolidating hyperinsulinemia and a hyperglycemic status.…”
Section: Discussionmentioning
confidence: 99%
“…There is a recognized association between diabetes and thyroid disease (Dimitriadis et al, 1997;Szkudelski, Michalski, & Szkudelska, 2003;Jin et al, 2004;Akbar, Ahmed, & Al-Mughales, 2006;Fernandez-Real et al, 2006). These are common endocrine disorders in Pakistani population.…”
Section: Introductionmentioning
confidence: 94%
“…The diabetic rats were divided randomly into two groups, one receiving vehicle alone and the other a daily intraperitoneal injection of T3 (10μg/kg/day). T3 was selected over thyroxine, because it mediates the effects of the latter in vivo and is more widely used in experimental animals (Carrillo-Sepúlveda et al, 2010;Dillmann, 1982;Hiroi et al, 2006;Szkudelski et al, 2003). Doses of 3μg/kg (considered physiological) and 30 or 50μg/kg (considered pharmacological) of T3 have been administrated daily to diabetic rats by others investigators (Dillmann, 1982;Szkudelski et al, 2003).…”
Section: Experimental Animalsmentioning
confidence: 99%
“…T3 was selected over thyroxine, because it mediates the effects of the latter in vivo and is more widely used in experimental animals (Carrillo-Sepúlveda et al, 2010;Dillmann, 1982;Hiroi et al, 2006;Szkudelski et al, 2003). Doses of 3μg/kg (considered physiological) and 30 or 50μg/kg (considered pharmacological) of T3 have been administrated daily to diabetic rats by others investigators (Dillmann, 1982;Szkudelski et al, 2003). Since 3μg/kg has no obvious metabolic effect, preliminary experiments were performed using 10μg/kg, 50μg/kg and 100μg/kg of T3, however, the latter two doses were severely toxic in diabetic rats, prompting the use of 10μg/kg/day for further studies.…”
Section: Experimental Animalsmentioning
confidence: 99%